DETERMINANT JOB INVOLVEMENT, AND CAREER DEVELOPMENT ON JOB SATISFACTION AND ITS IMPLICATIONS FOR ORGANIZATIONAL COMMITMENT - Nuraeni Nuraeni; M. Yusuf (Sosiohumaniora, 2023)
This study’s objective was to examine the impact of perceived organizational support, work participation, and career advancement on faculty lecturers’ job satisfaction and organizational commitment at Muhammadiyah Universities in Jabodetabek. This study employed a descriptive and verification survey with 1,402 faculty lecturers from Muhammadiyah Universities in Jabodetabek and a sample size of 420 respondents. SEM (Structural Equation Modeling) using Lisrel data analysis tools 8.80 is utilized to analyze the data. Based on the study’s results, the following conclusions were drawn: At Muhammadiyah Universities in Jabodetabek, perceived organizational support, work participation, and career advancement had a favorable and substantial influence on job satisfaction, with a contribution value (R2) of 60%. Partially, perceived organizational support has the greatest effect on lecturers’ work satisfaction, particularly those aspects of lecturer welfare that are indicated by caring characteristics. The perceived organizational support, job participation, career advancement, and work satisfaction of faculty lecturers at Muhammadiyah Universities in Jabodetabek have a positive and considerable influence on organizational commitment, with a contribution value (R2) of 86%. Partially, work satisfaction exerts the greatest effect on organizational commitment, as evidenced by the supervisor supervision dimension of job satisfaction. The results also demonstrated that work satisfaction mediates the influence of perceived organizational support, job participation, and career advancement on organizational commitment.